Museos y Facultades de Bellas Artes: didáctica para un reencuentro - Luelmo Jareño, José Mª De (Arte, Individuo y Sociedad, 2007)
From a contemporary perspective the basic aim of the museum is to extend the culture of quality to a public as diverse and wide as possible. Even more important must be its work with those groups related to the different levels of education. In this sense, there is a highly specific group which requires special attention, for it´s composed by people that in the near future could either take part in the activity of the museum or even to contribute to it through their own work: the studens of fine arts faculties. The relationship between this group and the museum offers as many points of juncture as misundersatandings, and it seems obvious that the bonds between them are demanding for a better and more consistent planification. In order to achieve this, the role of the universty teacher is a fundamental one.